Model evidence for a seasonal bias in Antarctic ice cores - Michael P. Erb; Charles S. Jackson; Anthony J. Broccoli; David W. Lea; Paul J. Valdes; Michel Crucifix; Pedro N. DiNezio (Nature Communications, 2018)
Periodic changes in the tilt of the Earth’s axis alter the distribution of incoming solar radiation. Here, the authors show that the temperature response to this forcing seemingly differs in models and Antarctic ice cores, with a better agreement reached if ice cores are recording a seasonally weighted signal.